2021
DOI: 10.3389/fsurg.2021.761441
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Morphology of the Coracoclavicular Joint: An Osteological Study of 2,724 Subjects Using Univariable and Multivariable Logistic Regression Analyses

Abstract: Background: The coracoclavicular joint (CCJ) is an anomalous articulation between the surfaces of the inferior clavicle and superior coracoid and its etiology is controversial. Reportedly, symptomatic patients demonstrate significant functional limitations including shoulder abduction loss and potential for brachial plexus compression and impingement.Purpose: To determine the prevalence of CCJ across age, gender and ethnicity, and to identify clinically useful morphological characteristics.Methods: 2,724 subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…By a large margin, males have a higher frequency of CCJ (661 cases) than females (223 cases) (Table 1). Interestingly, Harlow et al (2021) was the only study that found a higher frequency among females (10.8% vs. 8.1% for males). However, this difference did not appear in their multivariate model.…”
Section: Literature Reviewmentioning
confidence: 95%
See 4 more Smart Citations
“…By a large margin, males have a higher frequency of CCJ (661 cases) than females (223 cases) (Table 1). Interestingly, Harlow et al (2021) was the only study that found a higher frequency among females (10.8% vs. 8.1% for males). However, this difference did not appear in their multivariate model.…”
Section: Literature Reviewmentioning
confidence: 95%
“…In studies that tallied the number of bilateral versus unilateral cases, roughly half of the individuals with a CCJ had one on both sides (Harlow et al, 2021;Kaur & Jit, 1991;Nalla & Asvat, 1995;Nehme et al, 2004;Totlis et al, 2018;Yammine & Assi, 2015). Chopra (3.7%).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations